2020
DOI: 10.1186/s12889-020-09004-w
|View full text |Cite
|
Sign up to set email alerts
|

Trends, prevalence and associated factors of obesity among adults in a rural community in Thailand: serial cross-sectional surveys, 2012 and 2018

Abstract: Background: Obesity is one principle risk factor increasing the risk of noncommunicable diseases including diabetes, hypertension and atherosclerosis. In Thailand, a 2014 study reported obesity (BMI ≥25 kg/m 2) in a Thai population aged ≥15 years was 37.5, 32.9 and 41.8% overall and among males and females, respectively. The study aimed to determine trends in the prevalence of obesity among adults residing in a Thai rural community between 2012 and 2018 and investigate the associations between obesity and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…The relationship between smoking and obesity is complex, and published studies have produced conflicting results. Some reported current smokers were less likely to be obese than never smokers [ 27 ]; some have shown no significant association between smoking and body mass index [ 28 ]; our study is consistent with studies that have found that former smokers were more likely to be obese [ 29 ]. These contradictory findings show that the association still requires more attention.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between smoking and obesity is complex, and published studies have produced conflicting results. Some reported current smokers were less likely to be obese than never smokers [ 27 ]; some have shown no significant association between smoking and body mass index [ 28 ]; our study is consistent with studies that have found that former smokers were more likely to be obese [ 29 ]. These contradictory findings show that the association still requires more attention.…”
Section: Discussionsupporting
confidence: 91%
“…An outdoor lifestyle combined with mask wearing practices due to pre-existing environmental pollution was already in place before the pandemic [ 5 ]. Thailand’s efficient, robust, and responsive grassroots-level universal health care system, directed by able scientists, has greatly impacted preventive and treatment measures [ 6 ] even with a rising prevalence of pre-existing comorbidities like obesity, diabetes, and hypertension in the whole of the Mekong river region [ 7 , 8 ]. Others might argue that Thailand’s low testing frequency (19 tests per 1000 people) might underestimate the magnitude of the COVID-19 situation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might be because of a high prevalence of overweight and obesity in both men and women who participated in the study. As reported, the prevalence of obesity in Thailand keeps increasing from 33.9% in 2012 to 44.8% in 2018 even in rural areas [ 31 ]. With a sedentary lifestyle of our participants, the obesity prevalence is higher than expected.…”
Section: Discussionmentioning
confidence: 99%